2010
DOI: 10.1039/b927030b
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an heterochiral supramolecular cage by diastereomer self-discrimination: fluorescence enhancement and C60 sensing

Abstract: Diastereomer discrimination was observed in the formation of a metallomacrocycle from a racemic ligand based on Tröger's base. The metallomacrocycle exhibited a dramatic increase in fluorescence intensity compared to the ligand and its fluorescence was efficiently quenched by C(60).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…We decided to use racemic mixtures to synthesize rac-2 because in the crystal structures of iodo Tröger´s base derivatives formed by a single enantiomer, as reported in the Cambridge Structure Database, the acceptor in the halogen bonding is the electron density of the aromatic rings. 24,25 In contrast, in derivatives that contain the pair of enantiomers it is the nitrogen atoms that act as halogen bonding acceptors.…”
Section: 22mentioning
confidence: 99%
“…We decided to use racemic mixtures to synthesize rac-2 because in the crystal structures of iodo Tröger´s base derivatives formed by a single enantiomer, as reported in the Cambridge Structure Database, the acceptor in the halogen bonding is the electron density of the aromatic rings. 24,25 In contrast, in derivatives that contain the pair of enantiomers it is the nitrogen atoms that act as halogen bonding acceptors.…”
Section: 22mentioning
confidence: 99%
“…Formed as a racemic mixture, it is highly strained, where the two aryl groups are close to being orthogonal to each other. 2,3 Because of this, Tro¨ger's bases have a 'cleft-like' 4 structure, which have found their use in supramolecular chemistry; [4][5][6] where they have been employed as a structural scaffold for the formation of metallo-cages, 7 -heterochiral rhombs, 8 -aggregates, 9 -organic-frameworks (MOFS) 10 and -helicates. 11 They have also been used as building blocks in molecular tweezers, 12 calixarenes, 13 and various other rigid scaffolds.…”
mentioning
confidence: 99%
“…Whereas Fe III resulted in diastereomerically pure complexes, Zn II displayed no diastereoselectivity 29c. In a similar approach, Lützen and our own group built a metallomacrocycle from a racemic bis(4‐pyridyl‐alkyne)‐derived TB analogue (Figure 32) and (dpp)Pt(OTf) 2 in a diastereoselective self‐discrimination process, which formed exclusively the heterochiral R , R , S , S isomer 88. Our group showed that the resulting cage (Figure 32, right) displayed greatly enhanced fluorescence relative to the TB ligand alone.…”
Section: Other Applications Of Tröger's Basementioning
confidence: 98%
“…Goswani and Ghosh synthesized aminopyridine analogues by both approaches – Routes A and B in Scheme – to form the hydrogen‐bond receptor TB analogue 88 87. Approaches similar to Route A (Scheme ) have been developed for production of heterocyclic TB analogues (e.g., bis‐pyridinium analogues) 88. In addition, benzodiazolium TB analogues have been synthesized by an approach in which the heterocyclic functional group is introduced after the TB condensation has taken place 89…”
Section: Functionalization Of Tröger's Basementioning
confidence: 99%